PERAN PONDOK PESANTREN WARIA AL- FATAH DI KOTA GEDE YOGYAKARTA DALAM MENGURANGI DISKRIMINASI - Zahro Qoryatina Putri; Rachmad Kristiono Dwi Susilo; Muhammad Hayat (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
Humans as God's creatures have rights that must be obtained, besides that every human being as a citizen also has rights that must be obtained as citizens without having to look at gender, race, ethnicity, or religion. In Indonesia, transgender is a term for a man who looks and behaves like a woman. Waria in Indonesia are a minority group who often get discriminated against because their identity is not recognized. There is a public stigma that says that transgender is a deviant behavior resulting in a lot of acts of discrimination. This is the purpose of my research, which is to find out how the role of the Waria Al-Fatah Islamic Boarding School is in reducing discrimination by looking at the efforts made in providing training, education, experience, and in providing spiritual experience by using qualitative research types and study methods. Embedded cases or multiple cases are due to in-depth study of interactions between communities, organizations, communities by disclosing specific, detailed and detailed matters, besides not only understanding or researching a unique and distinctive case. The subjects of this study include the administrators of Islamic boarding schools listed on the organizational structure, transgender students, and also local residents who are directly adjacent to the activities of Islamic boarding schools. In this study using the theory of Culture Studies, Culture Studies is a theory that examines culture, the reason for using this theory is because the transgender Islamic boarding school is a product of cultural acceleration or Counter Culture. It is interpreted as a minority culture characterized by conflicting values, norms, and behaviors. The result of this research is that the Waria Al-Fatah Islamic Boarding School is a space that is able to provide security and comfort for its students to worship, learn about Islamic science, learn entrepreneurship, to capacity building.